Effect of Education Using Animation on the Ability to Develop Personal Skills for Early Stroke Detection and Initial Treatment at Home - Yoany Maria Vianney Bita Aty; Florentianus Tat; Gadur Blasius; Irfan Irfan; Pius Selasa; Trifonia Sri Nurwela (Ianna Journal of Interdisciplinary Studies)
Background: The success of stroke treatment depends on the speed and accuracy of early detection and prompt transportation to health facilities. However, many people have not received information on how to detect and treat the condition at home.